2011
DOI: 10.1155/2011/675858
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Prophylactic Vaccination against Cervical Cancer and Other Human Papillomavirus-Related Cancers in Developing Countries

Abstract: Cervical cancer and other human papillomavirus- (HPV-) related cancers are preventable, but preventive measures implemented in developing countries and especially in low-income rural regions have not been effective. Cervical cancer burden derived from sexually transmitted HPV infections is the heaviest in developing countries, and a dramatic increase in the number of cervical cancer cases is predicted, if no intervention is implemented in the near future. HPV vaccines offer an efficient way to prevent related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 110 publications
0
14
0
2
Order By: Relevance
“…According to reports from the major phase III trials, the vaccines prevent from 97 to 98% of infections caused by HPV-16 and -18 [27]. Investigators from the FUTURE (Females United to Unilaterally Reduce Ecto/Endocervical Disease) II study found a 98% protection rate after a 3-year follow-up period.…”
Section: The Current Situation With Regard To Prophylactic Hpv Vaccinmentioning
confidence: 99%
See 4 more Smart Citations
“…According to reports from the major phase III trials, the vaccines prevent from 97 to 98% of infections caused by HPV-16 and -18 [27]. Investigators from the FUTURE (Females United to Unilaterally Reduce Ecto/Endocervical Disease) II study found a 98% protection rate after a 3-year follow-up period.…”
Section: The Current Situation With Regard To Prophylactic Hpv Vaccinmentioning
confidence: 99%
“…Similarly, the incidence of cervical cancer and mortality rates sharply declined in Europe (particularly in Nordic countries) and Canada due to the implementation of cervical cytology in health care, most notably in population-based screening programs [27]. The establishment of cervical cancer trial programs requires a large number of well-trained professionals and persistent public funding to support the requisite infrastructure [30,89].…”
Section: The Impact Of Hpv Vaccination On Developing Countriesmentioning
confidence: 99%
See 3 more Smart Citations